Microhabitats, macro-differences: a survey of temperature records in Victoria Land terrestrial and freshwater environments - Cucini, Claudio; Nardi, Francesco; Magnoni, Letizia; Rebecchi, Lorena; Guidetti, Roberto; Convey, Peter; Carapelli, Antonio (Antarctic Science, 2022)
The temperature experienced by micro-invertebrates in extreme environments (such as those of Antarctica) is a pivotal parameter regarding these animals' ecology and physiology. However, at present, detailed knowledge of microhabitat physical conditions in Antarctica is limited, as well as being biased towards sub-Antarctic and Maritime Antarctic regions. To better understand the temperature conditions experienced in the microhabitats of Continental Antarctica by the native microfauna, we recorded temperatures year round in ponds and soils in an area of the Victoria Land coast and compared these measurements with air temperature data from the closest automatic weather station. We identified an important difference in temperature dynamics between the air, soil and pond datasets. Ponds were the warmest sites overall, differing by up to 7.5°C in comparison with the air temperature due to their greater thermal capacity, which also drove their patterns of freeze-thaw cycles and mean daily thermal excursion.